2018
DOI: 10.1038/s41598-018-31244-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor FokI polymorphism and the risks of colorectal cancer, inflammatory bowel disease, and colorectal adenoma

Abstract: Based on an inverse association between vitamin D levels and the risks of colorectal diseases, a functional start codon polymorphism in the vitamin D receptor (VDR) gene is speculated to affect the risks for these diseases. To validate this hypothesis, we first conducted a case-control study of 695 colorectal cancer patients and 1,397 controls. The association of VDR FokI polymorphism with colorectal cancer risk was analyzed using a logistic regression model. In the present case-control study, compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In addition, differences in the effect of calcitriol on the transcriptome of normal rectum and rectal tumor organoids were mainly on the level of gene expression. These findings appear to conflict with the reported links between genomic variation/polymorphisms in several vitamin D system genes ( VDR , GC , CYP24A1 , CYP2R1, and DHCR7/NADSYN1 ) and differences in the response to vitamin D compounds in studies involving CRC patients [ 68 , 69 , 70 , 71 , 72 , 73 ]. However, this discrepancy may again reflect differences between the in vivo and in vitro situations, since some vitamin D system genes play no role in cultured organoids; for example, the GC gene encodes the vitamin D binding protein, which is responsible for the blood transport of 25-hydroxyvitamin D/calcidiol and calcitriol.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, differences in the effect of calcitriol on the transcriptome of normal rectum and rectal tumor organoids were mainly on the level of gene expression. These findings appear to conflict with the reported links between genomic variation/polymorphisms in several vitamin D system genes ( VDR , GC , CYP24A1 , CYP2R1, and DHCR7/NADSYN1 ) and differences in the response to vitamin D compounds in studies involving CRC patients [ 68 , 69 , 70 , 71 , 72 , 73 ]. However, this discrepancy may again reflect differences between the in vivo and in vitro situations, since some vitamin D system genes play no role in cultured organoids; for example, the GC gene encodes the vitamin D binding protein, which is responsible for the blood transport of 25-hydroxyvitamin D/calcidiol and calcitriol.…”
Section: Discussionmentioning
confidence: 72%
“…2.0–2.9 μg in non‐users. Furthermore, recent studies have examined vitamin D receptor polymorphisms and risk of colorectal diseases and found different results for different disease entities, and a large Mendelian randomization study provides no evidence for a causal relationship between vitamin D and risk of colorectal cancers, although small effect sizes and non‐linear relationships cannot be ruled out. Like our study, none of these studies had information on potential confounding factors such as smoking habits, alcohol consumption, body fatness, physical activity or family history of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] Studies have shown that 1,25-D3 and the VDR suppress c-MYC function via regulating the c-MYC/MXD1 network, providing a molecular basis for cancer preventive actions of vitamin D. [20] Variants of VDR was found associate with tuberculosis, [21] osteoporosis [22] and cancers including colorectal cancer and LC. [23,24] Until now, certain VDR gene variants have been verified in relation to LC risk with different results including Fok1, Bsm1, Taq1, Apa1, Cdx2. In order to further provide theoretical support for the pathogenesis of LC, explore the association between Bsm1 (rs1544410 G>A), Apa1 (rs7975232 C>A), Taq1 (rs731236 T>C) and Cdx-2 (rs11568820 T>C) polymorphisms of VDR associations in relation to LC susceptibility was performed in this meta-analysis of 9 related studies.…”
Section: Introductionmentioning
confidence: 99%